ROLE OF SONOGRAPHY IN THE EVALUATION OF UNDESCENDED TESTIS IN PEDIATRICS (The Research of Medical Science Review, 2025)
Background: A condition in which one or both testicles fail to move from the abdomen, where they develop before birth, into the scrotum. A condition in which one or both testicles fail to move from the abdomen, where they develop before birth, into the scrotum. Undescended testicles may increase the risk for development of testicular cancer. Also called cryptorchidism. Undescended testicles may increase the risk for development of testicular cancer. Also called cryptorchidism. Cryptorchidism is the most prevalent congenital defect involving male genitalia and is characterized by the absence of at least one testicle from the scrotum. Approximately 3% of full-term and 30% of premature male infants are born with one or both testicles undescended. The Updated cost of undescended testicles in Pakistan ranging from 100k to 150k on one side and 150k to 200k on both sides.Objective: To determine the role of Sonography in evaluation of undescended testis in pediatrics.Methodology: The case-control analytical study was undertaken in which 94 patients‟ data were takes. The data was obtained from the radiology department of Lahore general Hospital. After obtaining informed consent, data was acquired via USG imaging using a Toshiba.Results: A total of 75 patients were included in our study 35 boys with 40 undescended testis were studied. The mean age of the boys at the time of surgery was 4.0 ± 0 years (range 1-11 years). Forty-six (88.5%) testes were localized pre-operatively by ultrasound- 20 of 22 (90.9%) palpable testes and 26 of 30 (86.7%) non-palpable testes. Intra-operatively, 49 (94.2%) of the undescended testes were found while 3 (5.8%) were absent/vanishing testes. Ultrasound evaluation had an accuracy of 86.5%, sensitivity of 89.8%, and specificity of 33.3%, PPV of 95.7% and a NPV of 16.7%.Conclusion: The role of Sonography in evaluation of undescended testis in pediatrics in patients above premature remains and area of ongoing research. Recent studies have focused on the visualization of in some cases about 20 percent of affected boys — an undescended testicle will descend (or “drop”) on its own within the child's first six months of life. Those that don't will require surgery.